Resilience in Relation to Adherence to Antiretroviral Therapy in People Living With HIV: A Qualitative Study - Anggri Noorana Zahra; Agung Waluyo; Sri Yona; Trevino Aristarkus Pakasi (SAGE Publishing, 2024)
Antiretroviral therapy (ART) adherence significantly impacts the survival and quality of life of people living with HIV (PLWH). Despite the challenges faced by PLWH, adherence remains crucial. Thus, cultivating resilience in ART is essential for optimal treatment outcomes. This qualitative study explored the experience of resilience in relation to ART adherence among PLWH. Semi-structured interviews with 10 participants were conducted and inductively analyzed. Participants' resilience in ART adherence was reflected in their achievements related to cultivating the habit of taking medication and in their convictions that the medication was a daily necessity. PLWH developed resilience through strategies encompassing finding purpose through faith and motivation, fostering wellness by obtaining adequate information, enjoying life, managing disease therapy, and adopting a healthy lifestyle, and building connections by finding adequate support and involving in the community. Nurses are crucial in HIV management, fostering resilience for successful ART adherence and ensuring effective treatment outcomes.